Rotating Brinkman hybrid nanofluid through an accelerated disk - Wan Nura’in Nabilah Noranuar,; Fasihah Zulkiflee,; Wan Nor Zaleha Amin,; Ahmad Qushairi Mohamad,; Rahimah Mahat,; Sharidan Shafie,; Noraihan Afiqah Rawi,; Lim, Yeou Jiann (Penerbit Universiti Kebangsaan Malaysia, 2025)
The prospective applications of mono nanofluids in heat transmission are greatly enhanced by their promising thermophysical characteristics. Changes in the ratio or concentration of the nanoparticles can modify the characteristics of mono nanofluids. However, the stable thermophysical properties were disclosed in the restricted range by the mono nanofluids, which only used one type of nanoparticles (metallic or non-metallic). Hybrid nanofluids have been created recently to address this weakness by enhancing the thermophysical features and heat transport capabilities of the basic fluid. The current investigation focuses the Brinkman hybrid nanofluid flow through an accelerated disk with the effect of rotation. Here, the considered hybrid nanofluid are the combination of alumina and copper nanoparticles suspending in water as the base fluid. The closed form solutions for governing momentum and energy equations have been attained with the help of Laplace transformations. Analysis of velocity and temperature distributions affected by the related parameters is carried out via graphical illustration, while the skin friction and Nusselt number are analysed in tables. The results expose that the primary and secondary velocity decelerates when imposing to the higher volume fraction of hybrid nanofluid parameter even though the heat transfer enhances. In addition, the results of both velocity and temperature distributions satisfied the imposed conditions.